The stingless bees of Santa Catarina State, Southern Brazil - Denise Monique Dubet da Silva Mouga; Enderlei Dec (Acta Biológica Catarinense, 2015)
Aiming to know the diversity of stingless bees in southern Brazil, a review of 27 publications, reporting sampling of stingless bees in the state of Santa Catarina, covering a period of 30 years, was performed. The studies have been related to plant formations where they took place. A total of 51 species of 17 genera were obtained, six species (with four subspecies) in the genus Melipona. The studies took place in 19 municipalities. The vegetation type where more collections were undertaken was the rain forest. Most surveys were performed in the southern and northern mesoregions. Differences in the number of species reported by different authors refer to genera Cephalotrigona, Frieseomelitta, Lestrimelitta, Melipona, Mourella, Nannotrigona, Oxytrigona, Paratrigona, Partamona, Plebeia, Scaptotrigona, Schwarziana, Tetragonisca and Trigona. The causes of the differences may include anthropogenic factors. Santa Catarina State, in view of the verified number of species, stands as the last high diversity spot for stingless bees in Brazil, in a northern-southern perspective.